PSORIASIS OF THE SCALP: METHODS OF TREATMENT AND CARE - A. I. Ermilova; R. M. Torkhshoeva; L. S. Namazova-Baranova (Вопросы современной педиатрии)
The results of the analysis of modern views on etiology, pathogenesis, classification and clinical manifestation of psoriasis are discussed in this article. The authors described the algorithm of assessment of severity of psoriasis by the means of PASI calculation. The data on different approaches to systematic and topical treatment of psoriasis according to the PASI values, as well as peculiarities of complications and disease course in patients with psoriasis of the scalp are shown. Assessment of efficacy of modern emollients as drugs of choice for the basic care of the skin of patients with psoriasis of the scalp is given.